Phänomenologischer Realismus. Voluntative und intentionalistische Realitätsbegründung bei Scheler und Husserl - Schwind Peter (Gestalt Theory, 2021)
In this text I argue that a phenomenological conception of reality cannot simply consider ‚reality’ to be a feature of the objects of our experience, nor can ‚reality’ be understood as a somehow subconscious experience of resistance, as Max Schelers notion of a „primary resistance“ tries to show. In opposition to these insufficient conceptions I suggest – following some husserlian inspirations – that the notion of ‚reality’ is to be understood as a elementary feature of our experience of objects – not of the objects of our experience. Is this perspective accepted, a minimal ‚realism’ appears as a presupposition of the concept of intentionality.